KYAI THOLHAH DAN GAGASAN PENYELAMATAN DAN PENGEMBANGAN FITRAH PESERTA DIDIK - Nunu Ahmad An-Nahidl (Badan Litbang dan Diklat Kementerian Agama RI, 2008)
This article highlights the inexistence of balance among the various education models in Indonesia. In one side, there is a practice of education that hardly emphasikes on studying and education of values and religious and ethical attitude and behavior but it is not balance with enough attention to the expansion of human basic potencies, like critical, creative, discipline, spirit [off achievement, and others. On the other side, there is an opinion of more emphasiking on improvement of thinking quality, expansion of rational attitudes, analytical and critical, but, according to him, less to care to saving effort and exploiting the student fitrah.